Suplemento pós-biótico no crescimento de tilápias-do-nilo - Cabanha, Fernando da Silva (2023)
The objective of this work was to analyze the growth of Nile tilapia and the water quality parameters using different doses of postbiotic in the masculinization period. 750 Nile tilapia post-larvae were cultivated for 33 days in a water recirculation system composed of 15 experimental units with a useful volume of 0.1m³. They were distributed in a completely randomized design consisting of five treatments and three replications, consisting of two diets including masculinizing hormone (60 mg of 17 α-methyltestosterone.kg-1) containing 0 and 2.5g/kg of postbiotic and three diets hormone-free containing 1.25; 2.5 and 3.75 of the additive. Water quality parameters were monitored daily. The data obtained were submitted to ANOVA 5%. At the end of the experiment it was verified that the results of biomass gain, weight gain, individual weight, average daily weight gain and specific growth had significant differences in both diets offered to fingerlings. Among the analyzed parameters of productive performance, the diets that did not contain masculinizing hormone with a dosage ≥2.5 g/kg of postbiotic showed the lowest values observed. The survival of the fingerlings did not show significant difference between the diets containing masculinizing hormone with 1,25 and 2.5 g/kg of postbiotic and without the additive. In all the physical and chemical parameters of the water analyzed, there were no significant differences between the results of the different treatments. Therefore, it is concluded that regardless of the doses of postbiotic included in the diet of the fingerlings, the water quality parameters remained in satisfactory conditions for the cultivation of the species and, for the zootechnical performance, the feeding using masculinizing hormone without the addition of postbiotic showed if superior presenting the most satisfactory values in the cultivation of Nile tilapia in the period of masculinization.